Chip-level underfill adhesive with low precipitation and excellent bonding performance and preparation method thereof

By adopting chip-grade underfill glue of specific formulas, including self-synthetic organosiloxane and epoxy resin, the problem of poor reliability in colloid precipitation and high temperature and high humidity environments in the prior art is solved, low precipitation, excellent adhesive performance and high heat resistance are achieved, and high reliability requirements for chip integrated packaging are met.

CN119570420APending Publication Date: 2025-03-07YANTAI DARBOND TECH

Patent Information

Application Number
CN202411745192.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing chip-level underfill glue has colloids during the filling process, resulting in poor appearance of packaging components and poor electrode conductivity, and poor reliability in high temperature and high humidity environments, making it difficult to meet the bonding strength and heat resistance requirements of advanced chip integrated packaging.

Method used

The chip-grade underfill formula with low precipitation and excellent bonding performance is adopted, including self-synthetic organosiloxanes, epoxy resins, coupling agents, black pastes, fillers and curing agents, and through specific synthetic paths and component ratios, the colloid has excellent bonding strength and flow properties under high temperature conditions.

Benefits of technology

It achieves low precipitation, excellent bonding performance and high heat resistance, meets the high reliability requirements of chip integrated packaging, avoids cracking and layering of colloids and substrates/chips, and ensures the stability and reliability of the packaged devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005163543930000021
    Figure BDA0005163543930000021
  • Figure BDA0005163543930000031
    Figure BDA0005163543930000031
  • Figure BDA0005163543930000032
    Figure BDA0005163543930000032
Patent Text Reader

Abstract

The invention belongs to the technical field of adhesives, and discloses a low-precipitation chip-scale bottom filling adhesive with excellent bonding performance and a preparation method, the filling adhesive comprises the following components by weight: 2-4 parts of self-synthesized organosiloxane, 30-35 parts of epoxy resin, 1-3 parts of a coupling agent, 1-2 parts of black paste, 60-65 parts of a filler, and 10-15 parts of a curing agent. Compared with the conventional chip-level underfill adhesive, the product provided by the invention has higher bonding strength on a silicon wafer and an LMC substrate; and after being placed in a Uhast environment box for 192 hours, the adhesive still has excellent bonding strength on silicon wafers and LMC substrates under a high-temperature condition. In addition, the product also has the characteristics of excellent flowing property, low precipitation and good heat resistance, and can fully meet the requirements of operability and high reliability of chip integrated packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a chip-level bottom filling adhesive with low precipitation and excellent bonding performance and a preparation method thereof. Background Art

[0002] As an advanced packaging material, chip-level underfill is widely used in CSP (Chip Scale Package) and BGA (Ball Grid Array) packaging. The glue is filled between the chip and the substrate to disperse the stress on the solder balls and relieve the stress concentration caused by the mismatch of thermal expansion coefficients between the chip and the substrate. It plays a key role in improving the reliability of semiconductor component packaging. With the high performance and intelligence of electronic equipment, the number of chips covered in electronic devices is increasing, the size of the chips used is getting larger, and the spacing between solder balls is getting smaller, which puts higher reliability and operability requirements on chip-level underfill materials. In the chip integration packaging process, in order to improve the wettability between the substrate surface and the chip-level underfill, the substrate needs to be plasma treated before filling the chip-level underfill. When filling the chip-level underfill on the plasma-treated substrate, there is a phenomenon that the colloidal components precipitate around the chip. Severe precipitation will not only cause poor appearance of the packaged components, but also cause poor conductivity of the electrodes in severe cases. As the size of packaged chips becomes larger and larger, the reliability of chip packaging faces more severe challenges under high temperature and high temperature and high humidity environments, resulting in more serious warping and reliability problems, such as delamination between the chip-level bottom filler and the silicon chip, which in turn causes the failure of the packaged device. Therefore, it is very important for advanced chip integrated packaging to improve the bonding strength of the chip-level bottom filler to the silicon chip and the substrate, and to improve the high temperature and high humidity resistance of the chip-level bottom filler. In summary, it is of great significance to the technical field to develop a chip-level bottom filler suitable for chip integrated packaging that has low precipitation, excellent bonding strength to silicon wafers and LMC substrates under high temperature conditions, and high reliability in high temperature and high humidity environments. Summary of the invention

[0003] The present invention aims to solve the above-mentioned deficiencies in the prior art and aims to provide a chip-level bottom filling adhesive with low precipitation and excellent bonding performance and a preparation method thereof.

[0004] To achieve the above objectives, the technical solutions adopted are as follows:

[0005] One of the purposes of the present invention is to provide a chip-level bottom filling adhesive with low precipitation and excellent bonding performance, which comprises the following components in parts by weight:

[0006] 2-4 parts of self-synthesized organosiloxane, 30-35 parts of epoxy resin, 1-3 parts of coupling agent, 1-2 parts of black paste, 60-65 parts of filler, and 10-15 parts of curing agent.

[0007] Furthermore, the self-synthesized organosiloxane is synthesized by combining the following raw materials in parts by weight: 485-495 parts of self-synthesized vinyl-terminated monomers, 0.8-1.0 parts of platinum catalysts, and 480-490 parts of trimethoxysilane.

[0008] Furthermore, the self-synthesized vinyl-terminated monomer is synthesized from the following raw materials in parts by weight: 30 to 36 parts of 2,4,6-trihydroxy-3-(4-hydroxyphenyl)propiophenone, 20 to 24 parts of acryloyl chloride, 90 to 95 parts of triethylamine, and 1980 to 1990 parts of dichloromethane.

[0009] Furthermore, the structural formula of the self-synthesized organosiloxane is:

[0010]

[0011] Furthermore, the self-synthesized organosiloxane is prepared by a two-step method, and its synthesis path is:

[0012] The first step: a self-synthesized vinyl-terminated monomer is prepared by hydrolyzing acryloyl chloride with 2,4,6-trihydroxy-3-(4-hydroxyphenyl)propiophenone. The reaction formula is:

[0013]

[0014] Step 2: The self-synthesized vinyl-terminated monomer synthesized in the first step is subjected to a hydrosilylation reaction with trimethoxysilane by platinum catalysis to obtain a self-synthesized organosiloxane. The reaction formula is:

[0015]

[0016] Furthermore, the epoxy resin is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin and naphthalene epoxy resin. The bisphenol A epoxy resin is preferably YL980 (epoxy equivalent: 182-188) of Mitsubishi Chemical of Japan, the bisphenol F epoxy resin is preferably SQE-8170 (epoxy equivalent: 152-158) of Shandong Shengquan Chemical, and the naphthalene epoxy resin is preferably HP4032D (epoxy equivalent: 138-142) of DIC Corporation of Japan.

[0017] Furthermore, the epoxy resin is a combination of bisphenol A epoxy resin, bisphenol F epoxy resin and naphthalene epoxy resin.

[0018] The beneficial effect of adopting the above two-step further scheme is: different types of epoxy resins are selected to make the glass transition temperature (Tg), bonding strength, tensile strength and modulus of the chip-level bottom filling glue reach a balance point, with excellent comprehensive performance.

[0019] Furthermore, the coupling agent is a silane coupling agent, specifically at least one of 3-(2,3-epoxypropyloxy)propylmethyldiethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, and dodecyltrimethoxysilane.

[0020] The beneficial effects of adopting the above further scheme are: the silane coupling agent is conducive to improving the wetting performance of the chip-level bottom filling glue on the substrate and improving the fluidity; improving the compatibility between the resin and the filler; improving the wettability of the chip-level bottom filling glue on the substrate and enhancing the bonding strength.

[0021] Furthermore, the black paste is a premix of carbon black and bisphenol A epoxy resin, specifically a premix of MA100 of Mitsubishi Corporation of Japan and YL980 of Mitsubishi Chemical of Japan, and the mass ratio of MA100 to YL980 is 1.5:8.5.

[0022] Furthermore, the curing agent is a liquid aromatic amine curing agent. The liquid aromatic amine curing agent is preferably dimethylthiotoluenediamine, and more preferably HARTCURE 30 from Jonson Fine Chemical.

[0023] The beneficial effects of adopting the above further scheme are: ensuring that the chip-level bottom filling glue has excellent flow properties, meeting the workability requirements of chip integrated packaging for the chip-level bottom filling glue; and meeting the requirements of curing temperature and curing speed required by the chip integrated packaging process.

[0024] Furthermore, the filler is spherical silica, preferably a spherical silica composition of different particle sizes. Spherical silica A is preferably spherical silica with an average particle size of 1.5 μm surface treated with 3-glycidyloxypropyltrimethoxysilane, more preferably SE5050-SEJ manufactured by Japan ADMATECHS Co., Ltd. Spherical silica B is preferably spherical silica with an average particle size of 100 nm surface treated with 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, more preferably YC100A-JGP manufactured by Japan ADMATECHS Co., Ltd. The mass ratio of spherical silica A:B is 15-20:1.1-1.5.

[0025] The beneficial effects of adopting the above further scheme are: spherical silica has better fluidity than non-spherical silica when the filler content is the same; a combination of silica micropowders of different particle sizes can maximize the amount of filler added when the viscosity is the same, so that the chip-level bottom filling glue has a lower CTE, thereby ensuring the reliability of chip integrated packaging.

[0026] The second object of the present invention is to provide a method for preparing a chip-level bottom filling adhesive with low precipitation and excellent bonding performance, comprising the following steps:

[0027] (1) Dissolve 30 to 36 parts of 2,4,6-trihydroxy-3-(4-hydroxyphenyl)propiophenone in 1320 to 1326 parts of dichloromethane. Subsequently, add 90 to 95 parts of triethylamine to the above solution and cool the mixture to 0°C in an ice-water bath, dissolve 20 to 24 parts of acryloyl chloride in the remaining dichloromethane and add dropwise to the above mixture. Subsequently, stir at 0°C for 15 minutes, then remove the ice-water bath, and stir the reaction at room temperature for 24 hours. Subsequently, evaporate the excess dichloromethane and precipitate the mixture into excess methanol. Dissolve the precipitated reactant in chloroform, filter to remove unreacted 2,4,6-trihydroxy-3-(4-hydroxyphenyl)propiophenone, and precipitate the resulting filtrate with methanol, and repeat this process twice. Finally, dissolve the obtained reactant in chloroform, evaporate the solvent, and obtain a self-synthesized vinyl-terminated monomer;

[0028] 485-495 parts of the self-synthesized vinyl-terminated monomer are dissolved in toluene, and 0.8-1.0 parts of a platinum catalyst are added; then 480-490 parts of trimethoxysilane are added dropwise, heated to 90° C. and maintained for 3 hours, the platinum catalyst is recovered by filtration, and the excess trimethoxysilane and solvent are removed by reduced pressure distillation, thereby preparing a self-synthesized organosiloxane;

[0029] (2) 2-4 parts of the self-synthesized organosiloxane obtained in step (1), 30-35 parts of epoxy resin, 1-3 parts of coupling agent, 1-2 parts of black paste, and 60-65 parts of filler are added into a stirring kettle, stirred evenly, and vacuumed for degassing; then the premix is ​​subjected to a three-roll process and a aging process to ensure that the filler is fully impregnated; the fully impregnated premix is ​​added together with 10-15 parts of a curing agent into a stirring kettle, stirred evenly, and vacuumed for degassing to prepare a chip-level bottom filling adhesive with low precipitation and excellent bonding performance.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] Compared with conventional chip-level bottom filling glue, the product of the present invention has higher bonding strength to silicon wafers and LMC substrates; after being placed in the Uhast environmental chamber for 192 hours, it still has excellent bonding strength to silicon wafers and LMC substrates under high temperature conditions. In addition, the product of the present invention also has the characteristics of excellent flowability, low precipitation, and good heat resistance; it can fully meet the workability and high reliability requirements of chip integrated packaging, and avoid cracking and delamination between the colloid and the substrate / chip during the chip packaging process, thereby causing the failure of the packaged device;

[0032] The raw material 2,4,6-trihydroxy-3-(4-hydroxyphenyl) propiophenone selected for the self-synthesized organosiloxane of the present invention is a bio-based raw material, which is green and environmentally friendly and conforms to the current concept of green development; the self-synthesized organosiloxane has twelve alkoxy groups in its molecular structure, and the alkoxy groups can form a silicon hydroxyl structure through a hydrolysis reaction, and then form hydrogen bonds with the substrate and the hydroxyl groups on the surface of the silicon dioxide, thereby enhancing the toughness of the material itself and improving the bonding strength of the material to the substrate; after being placed in a Uhast environmental chamber for 192 hours, the chip-level bottom filling glue still has excellent bonding strength to the silicon wafer and the LMC substrate under high temperature conditions. In addition, the alkoxy groups on the molecular structure of the self-synthesized organosiloxane can undergo a dealcoholization reaction with the hydroxyl groups on the surface of the silicon dioxide; the interaction force between the silicon dioxide microspheres is enhanced, and the strength and toughness of the material itself are improved; at the same time, the self-synthesized organosiloxane, as a cross-linking point to enhance the interaction force between the silicon dioxides, forms a cross-linking network between the silicon dioxide microspheres, which is beneficial to improve the obstruction and restraint of small molecular substances in the system, thereby achieving the effect of reducing precipitation. In addition, the self-synthesized organic siloxane molecular skeleton has a benzene ring structure, which can give the material outstanding mechanical strength and excellent thermal stability; the introduction of multiple silicon-oxygen bond structures in the molecular structure design gives the material excellent flexibility; thereby ensuring the chip integration packaging operability and high reliability requirements. DETAILED DESCRIPTION

[0033] The principles and features of the present invention are described below in conjunction with examples. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.

[0034] Example 1

[0035] The steps for preparing a chip-level bottom filler with low precipitation and excellent bonding performance are as follows:

[0036] (1) At room temperature, 30 parts of 2,4,6-trihydroxy-3-(4-hydroxyphenyl)propiophenone were dissolved in 1320 parts of dichloromethane by weight. Subsequently, 90 parts of triethylamine were added to the above solution and the mixture was cooled to 0°C by ice-water bath, and 20 parts of acryloyl chloride were dissolved in 660 parts of dichloromethane and added dropwise to the above mixture. Subsequently, the mixture was stirred at 0°C for 15 minutes, and then the ice-water bath was removed and the reaction was stirred at room temperature for 24 hours. Subsequently, the excess dichloromethane was evaporated and the mixture was precipitated into excess methanol. The precipitated reactant was dissolved in chloroform, the unreacted 2,4,6-trihydroxy-3-(4-hydroxyphenyl)propiophenone was filtered off, and the resulting filtrate was precipitated by methanol, and this process was repeated twice. Finally, the obtained reactant was dissolved in chloroform, the solvent was evaporated, and a self-synthesized vinyl-terminated monomer (43.67 parts; conversion rate: 78.6%) was obtained.

[0037] 485 parts of the self-synthesized vinyl-terminated monomer are dissolved in toluene, and 0.8 parts of a platinum catalyst are added; then 480 parts of trimethoxysilane are added dropwise, and the mixture is heated to 90°C and maintained for 3 hours. The platinum catalyst is recovered by filtration, and the excess trimethoxysilane and solvent are removed by reduced pressure distillation, thereby preparing a self-synthesized organosiloxane (904.21 parts; conversion rate: 93.7%).

[0038] (2) At room temperature, 4 parts of the self-synthesized organosiloxane obtained in step (1), 20 parts of bisphenol A epoxy resin YL980, 15 parts of bisphenol F epoxy resin SQE-8170, 2 parts of 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane, 2 parts of black paste (the mass ratio of MA100 to YL980 is 1.5:8.5), 60.4 parts of spherical silica SE5050-SEJ with an average particle size of 1.5 μm, and 4.6 parts of spherical silica YC100A-JGP with an average particle size of 100 nm are added into a stirring kettle, stirred evenly, and vacuumed for degassing; then the premix is ​​subjected to a three-roll process and a aging process to ensure sufficient infiltration of the filler; the premix is ​​mixed with 15 parts of HARTCURE 30 are sequentially put into a stirring kettle, stirred evenly, and vacuumed for degassing to obtain a chip-level bottom filling adhesive with low precipitation and excellent bonding performance of the present invention.

[0039] Example 2

[0040] The steps for preparing a chip-level bottom filler with low precipitation and excellent bonding performance are as follows:

[0041] (1) Same as Example 1.

[0042] (2) At room temperature, 4 parts of the self-synthesized organosiloxane obtained in step (1), 20 parts of bisphenol A epoxy resin YL980, 15 parts of naphthalene epoxy resin HP 4032D, 2 parts of N-phenyl-3-aminopropyltrimethoxysilane, 2 parts of black paste (the mass ratio of MA100 to YL980 is 1.5:8.5), 0.4 parts of spherical silica SE5050-SEJ6 with an average particle size of 1.5 μm, and 4.6 parts of spherical silica YC100A-JGP with an average particle size of 100 nm are added into a stirring kettle, stirred evenly, and vacuumed to degas; then the premix is ​​subjected to a three-roll process and a aging process to ensure sufficient infiltration of the filler; the premix and 15 parts of HARTCURE 30 are sequentially added into a stirring kettle, stirred evenly, and vacuumed to degas, to obtain a chip-level bottom filling adhesive with low precipitation and excellent bonding performance of the present invention.

[0043] Example 3

[0044] The steps for preparing a chip-level bottom filler with low precipitation and excellent bonding performance are as follows:

[0045] (1) Same as Example 1.

[0046] (2) At room temperature, 4 parts of the self-synthesized organosiloxane obtained in step (1), 20 parts of bisphenol F epoxy resin SQE-8170, 15 parts of naphthalene epoxy resin HP 4032D, 2 parts of dodecyltrimethoxysilane, 2 parts of black paste (the mass ratio of MA100 to YL980 is 1.5:8.5), 60.4 parts of spherical silica SE5050-SEJ with an average particle size of 1.5 μm, and 4.6 parts of spherical silica YC100A-JGP with an average particle size of 100 nm are added into a stirring kettle, stirred evenly, and vacuumed for degassing; then the premix is ​​subjected to a three-roll process and a aging process to ensure sufficient infiltration of the filler; the premix and 15 parts of HARTCURE 30 are sequentially added into a stirring kettle, stirred evenly, and vacuumed for degassing to obtain a chip-level bottom filling adhesive with low precipitation and excellent bonding performance of the present invention.

[0047] Example 4

[0048] The steps for preparing a chip-level bottom filler with low precipitation and excellent bonding performance are as follows:

[0049] (1) Same as Example 1.

[0050] (2) At room temperature, 4 parts of the self-synthesized organosiloxane obtained in step (1), 15 parts of bisphenol A epoxy resin YL980, 10 parts of bisphenol F epoxy resin SQE-8170, 10 parts of naphthalene epoxy resin HP 4032D, 2 parts of 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane, 2 parts of black paste (the mass ratio of MA100 to YL980 is 1.5:8.5), 60.4 parts of spherical silica SE5050-SEJ with an average particle size of 1.5 μm, and 4.6 parts of spherical silica YC100A-JGP with an average particle size of 100 nm are added into a stirring kettle, stirred evenly, and vacuumed for degassing; then the premix is ​​subjected to a three-roll process and a aging process to ensure sufficient infiltration of the filler; the premix is ​​mixed with 15 parts of HARTCURE 30 are sequentially put into a stirring kettle, stirred evenly, and vacuumed for degassing to obtain a chip-level bottom filling adhesive with low precipitation and excellent bonding performance of the present invention.

[0051] Comparative Example 1

[0052] Prepare chip-level underfill:

[0053] At room temperature, 15 parts of bisphenol A epoxy resin YL980, 10 parts of bisphenol F epoxy resin SQE-8170, 10 parts of naphthalene epoxy resin HP 4032D, 2 parts of 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane, 2 parts of black paste (the mass ratio of MA100 to YL980 is 1.5:8.5), 60.4 parts of spherical silica SE5050-SEJ with an average particle size of 1.5 μm, and 4.6 parts of spherical silica YC100A-JGP with an average particle size of 100 nm are put into a stirring tank, stirred evenly, and vacuumed for degassing; then the premix is ​​subjected to a three-roll process and a aging process to ensure sufficient infiltration of the filler; the premix and 15 parts of HARTCURE 30 are sequentially put into a stirring tank, stirred evenly, and vacuumed for degassing to obtain a chip-level bottom filling adhesive.

[0054] Comparative Example 2

[0055] Prepare chip-level underfill:

[0056] At room temperature, in parts by weight, 71634 parts of Evonik organosiloxane VPS, 15 parts of bisphenol A epoxy resin YL980, 10 parts of bisphenol F epoxy resin SQE-8170, 10 parts of naphthalene epoxy resin HP 4032D, 2 parts of N-phenyl-3-aminopropyltrimethoxysilane, 2 parts of black paste (the mass ratio of MA100 to YL980 is 1.5:8.5), 60.4 parts of spherical silica SE5050-SEJ with an average particle size of 1.5 μm, and 4.6 parts of spherical silica YC100A-JGP with an average particle size of 100 nm were put into a stirring kettle, stirred evenly, and vacuumed for degassing; then the premix was subjected to a three-roll process and a aging process to ensure sufficient infiltration of the filler; the premix was mixed with 15 parts of HARTCURE 30 are put into a stirring kettle in sequence, stirred evenly, and vacuumed to degas to obtain a chip-level bottom filling glue.

[0057] test

[0058] The performance of the chip-level underfill adhesives of the above-mentioned embodiments 1 to 4 of the present invention and comparative embodiments 1 to 2 were tested by the following experiments.

[0059] Test 1. Separation distance test

[0060] The substrate (30μm gap, silicon wafer / glass) was preheated at 100℃ for 5min, and 4 pens of 5mg glue were filled in the I-type dispensing, and 1 pens of 5mg glue were filled in the U-type dispensing; it was cured at 120℃ for 1 hour and then cured at 150℃ for 1.5 hours, and the precipitation distance was measured by optical microscope.

[0061] Test 2. Flow performance test

[0062] Glass is connected to glass through spacer balls, with a gap of 30um and a glass sheet size of 20*20mm. The flow performance of chip-level bottom filling glue in chip integrated packaging at 110°C is simulated, and the flow time for complete filling is recorded.

[0063] Test 3. Glass transition temperature test

[0064] The glass transition temperature was obtained by DMA measurement using a dual cantilever measurement mode, heating from -50 °C to 265 °C at a rate of 3 °C / min, an oscillation frequency of 1 Hz and an amplitude of 10 μm.

[0065] Test 4. Thermal Expansion Coefficient Test (CTE1 <Tg)

[0066] The thermal expansion coefficient is obtained by TMA test, with a temperature increase from -20°C to 280°C, a heating rate of 5°C / min, and the unit is ppm / °C. Tested according to ASTM D696.

[0067] Test 5.K1C test

[0068] K 1C The test is based on ASTM D5045 test standard, measured by single-edge notch bending technique of a universal testing machine, using a 3-point bending fixture and testing the sample at a crosshead speed of 10mm / min.

[0069] Test 6.260℃ thrust strength test

[0070] Bare silicon wafer: The 260℃ thrust strength is obtained by testing with a push-pull tester. The glue and the bare silicon wafer are cured and bonded through a specific mold, and then placed on a test platform and heated at 260℃ for 5 minutes for a thrust test. The test rate is 50mm / min and the test height is 20um.

[0071] LMC substrate: The 260℃ thrust strength is obtained by testing with a push-pull tester. The glue is cured and bonded to the LMC substrate through a specific mold. The substrate is placed on a test platform and heated at 260℃ for 5 minutes. The thrust test is then performed at a test rate of 50mm / min and a test height of 20um.

[0072] Test 7. Uhast 192h 260℃ thrust strength test

[0073] Bare silicon wafer: The 260℃ thrust strength after Uhast 192h is obtained by testing with a push-pull tester. The glue and bare silicon wafer are cured and bonded through a specific mold. After being placed in the Uhast environmental chamber for 192 hours, it is placed on the test platform and heated at 260℃ for 5 minutes for thrust testing. The test rate is 50mm / min and the test height is 20um.

[0074] LMC substrate: The 260℃ thrust strength of Uhast after 192h is obtained by testing with a push-pull tester. The glue is cured and bonded to the LMC substrate through a specific mold. After being placed in the Uhast environmental chamber for 192 hours, it is placed on the test platform and heated at 260℃ for 5 minutes for a thrust test. The test rate is 50mm / min and the test height is 20um.

[0075] The results of tests 1 to 7 are shown in Table 1.

[0076] Table 1. Comparison of test performance of samples in Examples 1 to 4 and samples in Comparative Examples 1 to 2

[0077]

[0078] It can be seen from the data in Table 1 that the product of the present invention has higher bonding strength to silicon wafers and LMC substrates; after being placed in the Uhast environmental chamber for 192 hours, it still has excellent bonding strength to silicon wafers and LMC substrates under high temperature conditions, meeting the high reliability requirements of chip integrated packaging for chip-level bottom filling glue. In addition, the product of the present invention has the characteristics of low precipitation and excellent flowability, which can meet the stringent operational requirements of chip integrated packaging. It has good toughness and excellent mechanical properties, good heat resistance, and low CTE, which reduces the stress on the solder joints caused by the mismatch of the thermal expansion coefficients of the chip and the substrate, and effectively ensures the reliability of chip integrated packaging.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A chip-level underfill with low precipitation and excellent bonding performance, characterized in that: The invention comprises the following components in parts by weight: 2-4 parts of self-synthesized organic siloxane, 30-35 parts of epoxy resin, 1-3 parts of coupling agent, 1-2 parts of black paste, 60-65 parts of filler and 10-15 parts of curing agent.

2. The chip-level underfill adhesive with low precipitation and excellent bonding performance according to claim 1, characterized in that: The self-synthesized organic siloxane is prepared by compounding the following raw materials in parts by weight: 485-495 parts of self-synthesized vinyl-terminated monomers, 0.8-1.0 parts of platinum catalysts, and 480-490 parts of trimethoxysilane.

3. The chip-level underfill adhesive with low precipitation and excellent bonding performance according to claim 2, characterized in that: The self-synthesized vinyl-terminated monomer is prepared by combining the following raw materials in parts by weight: 30-36 parts of 2,4,6-trihydroxy-3-(4-hydroxyphenyl)propiophenone, 20-24 parts of acryloyl chloride, 90-95 parts of triethylamine, and 1980-1990 parts of dichloromethane.

4. The chip-level underfill adhesive with low precipitation and excellent bonding performance according to claim 1, characterized in that: The structural formula of the self-synthesized organosiloxane is:

5. The chip-level underfill adhesive with low precipitation and excellent bonding performance according to claim 4, characterized in that: The synthesis reaction of the self-synthesized organosiloxane is:

6. The chip-level underfill adhesive with low precipitation and excellent bonding performance according to claim 1, characterized in that: The epoxy resin is a combination of bisphenol A epoxy resin, bisphenol F epoxy resin and naphthalene epoxy resin.

7. The chip-level underfill adhesive with low precipitation and excellent bonding performance according to claim 1, characterized in that: The coupling agent is at least one of 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, and dodecyltrimethoxysilane; the black paste is a premix of carbon black and bisphenol A epoxy resin; and the curing agent is a liquid aromatic amine curing agent.

8. The chip-level underfill adhesive with low precipitation and excellent bonding performance according to claim 1, characterized in that: The filler is a composition of spherical silica with different particle sizes, wherein the mass ratio of spherical silica with an average particle size of 1.5 μm to spherical silica with an average particle size of 100 nm is 15-20:1.1-1.5; the surface of the spherical silica is epoxidized.

9. A method for preparing a chip-level underfill adhesive with low precipitation and excellent bonding performance according to any one of claims 1 to 8, characterized in that: The steps include: (1) 30 to 36 parts of 2,4,6-trihydroxy-3-(4-hydroxyphenyl)propiophenone are dissolved in 1320 to 1326 parts of dichloromethane; then, 90 to 95 parts of triethylamine are added to the above solution and the mixture is cooled to 0°C in an ice-water bath, 20 to 24 parts of acryloyl chloride are dissolved in the remaining dichloromethane and added dropwise to the above mixture; then, the mixture is stirred at 0°C for 15 minutes, and then the ice-water bath is removed and the mixture is stirred and reacted at room temperature for 24 hours. Subsequently, the excess dichloromethane is evaporated and the mixture is precipitated into excess methanol; the precipitated reactant is dissolved in chloroform, the unreacted 2,4,6-trihydroxy-3-(4-hydroxyphenyl)propiophenone is filtered off, and the resulting filtrate is precipitated with methanol, and this process is repeated twice; finally, the obtained reactant is dissolved in chloroform, the solvent is evaporated, and a self-synthesized vinyl-terminated monomer is obtained; 485-495 parts of the self-synthesized vinyl-terminated monomer are dissolved in toluene, and 0.8-1.0 parts of a platinum catalyst are added; 480-490 parts of trimethoxysilane are then added dropwise, and the mixture is heated to 90° C. and maintained for 3 hours. The platinum catalyst is recovered by filtration, and the excess trimethoxysilane and solvent are removed by distillation under reduced pressure, thereby preparing a self-synthesized organosiloxane; (2) 2-4 parts of the self-synthesized organosiloxane obtained in step (1), 30-35 parts of epoxy resin, 1-3 parts of coupling agent, 1-2 parts of black paste, and 60-65 parts of filler are added to a stirring kettle, stirred evenly, and vacuumed for degassing; the premix is ​​then subjected to a three-roll process and a aging process to ensure sufficient impregnation of the filler; the fully impregnated premix is ​​added together with 10-15 parts of a curing agent into a stirring kettle, stirred evenly, and vacuumed for degassing to prepare a chip-level bottom filling adhesive with low precipitation and excellent bonding performance.

Citation Information

Patent Citations

  • High-stability in-situ prepared primer for silane modified building sealant

    CN111117411A

  • Underfill adhesive as well as preparation process and application thereof

    CN113088230A

  • Bio-based chip-scale underfill adhesive suitable for large-size chip packaging and preparation method thereof

    CN114958262A

  • Low-stress underfill adhesive capable of being repaired by heating as well as preparation method and application of underfill adhesive

    CN117362597A

  • Chip-level underfill adhesive suitable for 2.5 D heterogeneous integrated packaging and preparation method thereof

    CN118725797A

Cited By

  • Bottom filling adhesive for packaging large-size chip, preparation method of bottom filling adhesive and packaging structure

    CN120795851A